Quercitrin Attenuates Acetaminophen-Induced Acute Liver Injury by Maintaining Mitochondrial Complex I Activity - Xiong, Weichen; Yuan, Zixin; Wang, Tianshun; Wu, Songtao; Xiong, Yiyi; Yao, Yunfeng; Yang, Yanfang; Wu, Hezhen (Frontiers in Pharmacology, 2021)
The flavonoid quercitrin has a strong antioxidant property. It is also reported to have a protective effect on the liver. However, the mechanism by which it exerts a protective effect on the liver is not clearly understood. The objective of this article is to confirm the protective effect of quercitrin extracted from Albiziae flos on Acetaminophen (APAP)-induced liver injury and to explain its mechanism. In the in vivo study, quercitrin was administered orally to BALB/c mice at a dose of 50, 100, 200 mg/kg for 7 consecutive days. APAP (300 mg/kg) was injected intraperitoneally after the last dose of quercitrin was administered. Determination of alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), interleukin 6 (IL-6) , tumor necrosis factor α (TNF-α), reactive oxygen species (ROS), superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GSH-Px), catalase (CAT) and malondialdehyde (MDA) levels showed that quercitrin can effectively attenuated APAP-induced acute liver injury in mice. Results of the in vitro study demonstrated that quercitrin reduced the levels of ROS and restored the activity of mitochondrial complex I in APAP treated L-02 cells. The addition of rotenone which is an inhibitor of complex I blocked the protective effect of quercitrin. The expression of mitochondrial complex I was also maintained by quercitrin. Results from our study demonstrated that the mechanism of action of quercitrin was found to maintain the level of mitochondrial complex I in injured cells and restore its activity. This reduced the production of ROS, protected the mitochondria from oxidative stress and had a protective effect on the liver.